Effect of microstructure on the mechanical properties and corrosion resistance of a welded joint of 620-grade marine steel - Dong, Yifan; Liu, Denghui; Du, Hegang; Sun, Haoran; Zuo, Xiurong (Frontiers in Materials, 2023)
The relationship between microstructure and mechanical and corrosion properties of welded joint of 620-grade marine steel was studied by metallographic microscopy, scanning electron microscopy, energy dispersive spectrometer, transmission electron microscopy, the microhardness and tensile tests. The results show that the strength and hardness of weld center area (WMmid) are higher than those of inner and outer welding surface region (WMin and WMout), due to the average size and volume fraction of martensite-austenite (MA) constituents (0.99 μm and 21.6%) higher than those in WMin and WMout (0.72 μm and 18.0%, 0.86 μm and 14.3%, respectively). There are numerous MnO-Al2O3-SiO2-TiO2 type inclusions located at the bottom of dimples, however, MA constituents take precedence over this kind of inclusions in inducing the pitting corrosion. In contrast, the pitting corrosion can originate from Al2O3-MgO-CaO-CaS inclusions in the heat affected zone (HAZ) and base metal (BM). The corrosion resistance of welded joint is in the order by weld metal＞HAZ＞BM. The WMmid with the smaller dendrite spacing had the better corrosion resistance, compared with WMin and WMout. The corrosion resistance of HAZ decreases in sequence of coarse grain HAZ, fine grain HAZ, intercritical HAZ with the decrease of peak temperature during welding.